Sex-dependent mental illnesses and mitochondria - Shimamoto, Akiko (Schizophr Res, 2017)
The prevalence of some mental illnesses, including major depression, anxiety-, trauma-, and stress-related disorders, some substance use disorders, and later onset of schizophrenia, is higher in women than men. While the higher prevalence in women could simply be explained by socioeconomic determinants, such as income, social status, or cultural background, extensive studies show sex differences in biological, pharmacokinetic, and pharmacological factors contribute to females’ vulnerability to these mental illnesses. In this review, we focus on estrogens, chronic stress, and neurotoxicity from behavioral, pharmacological, biological, and molecular perspectives to delineate the sex differences in these mental illnesses. Particularly, we investigate a possible role of mitochondrial function, including biosynthesis, bioenergetics, and signaling, on mediating the sex differences in psychiatric disorders.